CONTSEPT IS THE "LAUGHTER" AS SCLADNIC OF INTERPERSONALITY COMMUNICATIONS IN AN ARTISTIC TEXT (ON MATERIAL OF PROSE OF BEGINNING OF XXI AGE) - Danylyuk, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals the peculiarities of actualization the concept "laughing" in the interpersonal communication, analyzes character of it realization through the inner addressee and sender, investigates the laughter’s functional load in the text.